The impact of the health emergency on the process of inclusion of foreign students with disabilities - Diletta Chiusaroli (University of Bologna, 2020)
The inclusion in school of foreign minors with disabilities is a very complex and extremely contemporary issue. In particular, the push for research and its in-depth analysis was born in response to the need to find possible solutions capable of making the Italian education system as inclusive as possible, enhancing individual differences and ensuring the full educational success of all students, as it is established in constitutional principles. Through an analysis of the scientific literature, it is possible to outline the complexity of the phenomenon. The use of distance learning, in this period of health emergency, highlighted a series of problems that made the implementation of inclusive processes even more complex, such as, for example, the implications deriving from the digital divide. This work has the objective of analyzing the solutions identified by different educational institutions and gathering the experiences of teachers regarding the inclusive strategies adopted in distance learning. The purpose of this research is to identify any critical issues but also to trace possible ideas and good practices useful to increase the quality of inclusive learning paths aimed at foreign students with disabilities.